PENGARUH DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR PERKEBUNAN - Dewi, Sucitra; Rahman, Fauziah (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
The purpose of this study was to determine the effect of debt to equity ratio and current ratio on financial distress partially and simultaneously. The population in this study were manufacturing companies in the Plantation sub-sector in 2020-2022 as many as 24 companies with sampling techniques based on criteria using purposive sampling. The sample obtained based on the criteria was 72 food and beverage sub-sector companies. This type of research is quantitative with a causal associative approach. The data analysis technique used is quantitative with descriptive statistics using IBM SPSS and financial reports through the company's official website. The results stated that the debt to equity ratio had no effect on financial distress, while the current ratio partially had a negative and significant effect on financial distress. And the debt to equity ratio and current ratio simultaneously have a positive and significant effect on financial distress